UNDERSTANDING OF THE AYNA ALLAH HADITH: AN INTERDISCIPLINARY TAḤLĪLĪ STUDY - Azhary, Muhammad Royyan Faqih; Mashur, Mashur; Falah, Fajrul (Nabawi: Journal of Hadith Studies, 2024)
The Hadith ‘Aina Allah’ narrated by Abu Dawud has been debated because it is considered to contradict the rule that traditions that contradict the Quran cannot be used as proof. However, Abu Dawud himself states that this tradition is valid and can be used as an argument. This study aims to examine the compatibility between the Hadith ‘Aina Allah’ and the Quran, and to understand the Hadith through an interdisciplinary approach, including the perspectives of linguistics, creed, fiqh, and morals and Sufism. The method used is descriptive qualitative content analysis, with a literature review of Sunan Abu Dawud as the main source. The results show that the Hadith ‘Aina Allah’ is valid and does not contradict the Quran, but needs to be understood in a linguistic and rhetorical context that emphasises the high position of Allah in a symbolic sense. From the perspective of creed, this hadith allows testing one's faith through signs without the necessity of the two sentences of the creed. From the perspective of jurisprudence, it shows that vows are valid if they are in accordance with reality and that freeing a believing slave is better than a disbelieving slave. The moral and Sufism perspectives emphasise the importance of conveying knowledge according to one's intellect and avoiding prejudice without evidence. The study concludes that an interdisciplinary approach provides a richer understanding of this hadith and dispels the notion of contradiction with the Quran.[Hadis "Aina Allah" riwayat Abu Dawud menimbulkan perdebatan karena dianggap bertentangan dengan kaidah bahwa hadis yang berlawanan dengan Al-Quran tidak dapat dijadikan hujjah. Namun, Abu Dawud sendiri menyatakan bahwa hadis ini sahih dan dapat dijadikan hujjah. Penelitian ini bertujuan untuk mengkaji kesesuaian antara hadis "Aina Allah" dan Al-Quran, serta memahami hadis tersebut melalui pendekatan interdisipliner, mencakup perspektif linguistik, akidah, fikih, serta akhlak dan tasawuf. Metode yang digunakan adalah analisis konten kualitatif deskriptif, dengan telaah literatur dari Sunan Abu Dawud sebagai sumber utama. Hasil penelitian menunjukkan bahwa hadis "Aina Allah" memiliki kualitas sahih dan tidak bertentangan dengan Al-Quran, melainkan perlu dipahami dalam konteks linguistik dan retorika yang menekankan posisi tinggi Allah dalam makna simbolis. Dari perspektif akidah, hadis ini memperbolehkan pengujian keimanan seseorang melalui isyarat tanpa keharusan dua kalimat syahadat. Dari perspektif fikih, hadis ini menunjukkan bahwa nazar sah jika sesuai dengan realita, dan memerdekakan budak beriman lebih baik daripada budak kafir. Perspektif akhlak dan tasawuf menekankan pentingnya menyampaikan pengetahuan sesuai dengan kemampuan akal seseorang, serta menghindari prasangka buruk tanpa bukti. Penelitian ini menyimpulkan bahwa pendekatan interdisipliner memberikan pemahaman yang lebih kaya terhadap hadis ini, serta menghilangkan anggapan adanya kontradiksi dengan Al-Quran.]